A particle is projected vertically upwards and it reaches the maximum height $ H $ in time $ T $ seconds. The height of the particle at any time $ t $ will be
(A) $ g{(t - T)^2} $
(B) $ H - \dfrac{1}{2}g{(t - T)^2} $
(C) $ \dfrac{1}{2}g{(t - T)^2} $
(D) $ H - g{(t - T)^2} $
Answer
Verified
460.8k+ views
Hint : At the highest point, the velocity of the particle will be zero and the displacement will have the maximum value, i.e. $ H $ . We will use the formulas of projectile motion in a plane to get the required equations.
Formula used:
$\Rightarrow v = u + at $
where $ v $ is the final velocity of the particle, $ u $ is the initial velocity of the particle, $ a $ is the acceleration acting on the particle, and $ t $ is the time of action and for the calculation of the final velocity.
$\Rightarrow S = ut + \dfrac{1}{2}a{t^2} $ ,
where $ S $ is the displacement of the body and the rest of the notations are the same as in the above equation.
Complete step by step answer
Applying the formula $ v = u + at $ at the topmost point, we get
$\Rightarrow 0 = U + ( - g)T $
$ \Rightarrow U = gT $ ,
where $ U $ is the initial velocity of the particle.
Applying the formula $ S = ut + \dfrac{1}{2}a{t^2} $ at the topmost point again, we get
$\Rightarrow H = UT + \dfrac{1}{2}( - g){T^2} $
Putting the value of the initial velocity $ U $ as found above, we get
$\Rightarrow H = (gT)T - \dfrac{1}{2}g{T^2} $
$\Rightarrow H = \dfrac{1}{2}g{T^2} $ .
We will use these values in the general equation of motion $ S = ut + \dfrac{1}{2}a{t^2} $ , so that at a general height $ h $ , we get the required equation as
$\Rightarrow h = Ut + \dfrac{1}{2}( - g){t^2} $ ,
substituting $ U = gT $ , we get
$\Rightarrow h = gTt - \dfrac{1}{2}g{t^2} $
Adding $ 0 = H - \dfrac{1}{2}g{T^2} $ to the above equation we get,
$\Rightarrow h = gTt - \dfrac{1}{2}g{t^2} + H - \dfrac{1}{2}g{T^2} $
$\Rightarrow h = H + (gTt - \dfrac{1}{2}g{t^2} - \dfrac{1}{2}g{T^2}) $
On rearranging the equation further, we get,
$\Rightarrow h = H - \dfrac{1}{2}g( - 2Tt + {t^2} + {T^2}) $
$\Rightarrow h = H - \dfrac{1}{2}g{(t - T)^2} $
Therefore, the correct answer is option (B); $ H - \dfrac{1}{2}g{(t - T)^2} $ .
Note
The answer obtained is symmetric for a time of $ T $ before and after the value of $ t = T $ . This means that the value of the height of the particle will be the same at $ t = 0 $ and at $ t = 2T $ . This indicated that the displacement of the particle will start from $ 0 $ , reach the highest value of $ H $ at $ t = T $ , and then decrease, at the same rate of increase, to $ 0 $ at $ t = 2T $ .
Formula used:
$\Rightarrow v = u + at $
where $ v $ is the final velocity of the particle, $ u $ is the initial velocity of the particle, $ a $ is the acceleration acting on the particle, and $ t $ is the time of action and for the calculation of the final velocity.
$\Rightarrow S = ut + \dfrac{1}{2}a{t^2} $ ,
where $ S $ is the displacement of the body and the rest of the notations are the same as in the above equation.
Complete step by step answer
Applying the formula $ v = u + at $ at the topmost point, we get
$\Rightarrow 0 = U + ( - g)T $
$ \Rightarrow U = gT $ ,
where $ U $ is the initial velocity of the particle.
Applying the formula $ S = ut + \dfrac{1}{2}a{t^2} $ at the topmost point again, we get
$\Rightarrow H = UT + \dfrac{1}{2}( - g){T^2} $
Putting the value of the initial velocity $ U $ as found above, we get
$\Rightarrow H = (gT)T - \dfrac{1}{2}g{T^2} $
$\Rightarrow H = \dfrac{1}{2}g{T^2} $ .
We will use these values in the general equation of motion $ S = ut + \dfrac{1}{2}a{t^2} $ , so that at a general height $ h $ , we get the required equation as
$\Rightarrow h = Ut + \dfrac{1}{2}( - g){t^2} $ ,
substituting $ U = gT $ , we get
$\Rightarrow h = gTt - \dfrac{1}{2}g{t^2} $
Adding $ 0 = H - \dfrac{1}{2}g{T^2} $ to the above equation we get,
$\Rightarrow h = gTt - \dfrac{1}{2}g{t^2} + H - \dfrac{1}{2}g{T^2} $
$\Rightarrow h = H + (gTt - \dfrac{1}{2}g{t^2} - \dfrac{1}{2}g{T^2}) $
On rearranging the equation further, we get,
$\Rightarrow h = H - \dfrac{1}{2}g( - 2Tt + {t^2} + {T^2}) $
$\Rightarrow h = H - \dfrac{1}{2}g{(t - T)^2} $
Therefore, the correct answer is option (B); $ H - \dfrac{1}{2}g{(t - T)^2} $ .
Note
The answer obtained is symmetric for a time of $ T $ before and after the value of $ t = T $ . This means that the value of the height of the particle will be the same at $ t = 0 $ and at $ t = 2T $ . This indicated that the displacement of the particle will start from $ 0 $ , reach the highest value of $ H $ at $ t = T $ , and then decrease, at the same rate of increase, to $ 0 $ at $ t = 2T $ .
Recently Updated Pages
Questions & Answers - Ask your doubts
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Master Class 11 Science: Engaging Questions & Answers for Success
Full Form of IASDMIPSIFSIRSPOLICE class 7 social science CBSE
In case of conflict between fundamental rights of citizens class 7 social science CBSE
Can anyone list 10 advantages and disadvantages of friction
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
What is the specific heat capacity of ice water and class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE